2010
DOI: 10.1038/aps.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin inhibits homocysteine-induced dysfunction and apoptosis in endothelial progenitor cells

Abstract: Aim: To investigate the protective effects of atorvastatin on homocysteine (Hcy)-induced dysfunction and apoptosis in endothelial progenitor cells (EPCs) and the possible molecular mechanisms. Methods: EPCs were divided into six groups: Hcy treatment groups (0, 50, and 500 μmol/L) and atorvastatin pretreatment groups (0.1, 1, and 10 μmol/L). EPC proliferation, migration, in vitro vasculogenesis activity, and apoptosis rate were assayed by the MTT assay, modified Boyden chamber assay, in vitro vasculogenesis ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
5
21
0
Order By: Relevance
“…1a and b, cellular migration and proliferation of EPCs were inhibited by incubation with 500 μmol/L Hcy for 24 h compared with the control group. The results were consistent with our previous work [18]. However, here we found these detrimental effects of Hcy on EPCs were attenuated by AICAR (0.5 and 1 mmol/L) pretreatment for 1 h (Fig.…”
Section: Activation Of Ampk Attenuated the Detrimental Effects Of Hcysupporting
confidence: 94%
See 1 more Smart Citation
“…1a and b, cellular migration and proliferation of EPCs were inhibited by incubation with 500 μmol/L Hcy for 24 h compared with the control group. The results were consistent with our previous work [18]. However, here we found these detrimental effects of Hcy on EPCs were attenuated by AICAR (0.5 and 1 mmol/L) pretreatment for 1 h (Fig.…”
Section: Activation Of Ampk Attenuated the Detrimental Effects Of Hcysupporting
confidence: 94%
“…Compared with the control, 500 μmol/L Hcy significantly increased ROS accumulation (Fig. 3a), which was consistent with our previous work [18]. Here we found that this effect could be markedly blunted by AICAR (0.5 and 1 mmol/L) (Fig.…”
Section: Ampk Activation Prevented Ros Accumulation and Nox4 Activatisupporting
confidence: 92%
“…However, the mechanisms responsible for this association are incompletely understood. A leading hypothesis is that homocysteine increases oxidative stress and impairs endothelial function (Bao et al, 2010). Our data showed that HFD significantly increased plasma homocysteine concentration.…”
Section: Discussionsupporting
confidence: 47%
“…19,20 or upregulating Akt signaling. 21,38,39 We provide experimental evidence that the dysfunction of BM EPCs from subjects with PGF after allo-HSCT is related to the activation of the p38 MAPK pathway and its downstream transcription factor CREB. By contrast, no significant differences were detected in phospho-JNK, ERK, or Akt levels between subjects with PGF and GGF.…”
Section: Discussionmentioning
confidence: 96%